A preliminary study to investigate the number of elite dressage riders competing in pain in the United Kingdom - Lewis, V.; Davies, E.; Kennerley, R. (DCA Report; Nr. 044, 2014)
Equestrianism is more dangerous than many sports including motorcycle riding, skiing, football and rugby with one in five equestrians seriously injured during their riding career. In addition to the high injury incident rate which could cause the rider to experience acute pain, saddle design and the lifestyle of elite riders could further aggravate the symptoms of chronic pain. An elite rider suffering from pain may still choose to compete with pain due to the pressures from sponsors and owners and the need for competition success to promote the rider and support the rider financially. The welfare of the rider needs to be considered and continuing to ride with pain is an issue which British Dressage needs to address. Therefore, this study is a preliminary study which aims to identify the number of elite dressage riders competing with pain in the United Kingdom which should provide British Dressage with an incentive to develop sports medicine, education for coaches, rehabilitation techniques for the rider and improve ergonomic technology, all of which would increase performance. In order to meet the aim of this study, a quantitative approach was used due to the experimental nature of the study. Questionnaires were distributed to 50 elite dressage riders at the Festival of Dressage located at Hartpury College to establish the prevalence of competing with pain. In order to achieve the most reliable results, professional elite dressage riders were used as the lifestyle and workload of these riders is more likely to be standardised in comparison to amateur riders. 74% of elite dressage riders compete while experiencing pain. Pearson`s Chi2 Test was used to identify any associations and statistical significance was set at P<0.05. There was a highly significant relationship between competing with pain and pain affecting negatively on performance (X2=16.216a, df=1, P= 0.000) and the rider experiencing pain and the treatment of pain (X2=50.000a, df=4, P=0.000). Further research is needed to determine why riders continue to compete with pain; the impact competing with pain has on rider performance; the design of dressage ergonomics and to identify a method of treatment of pain which riders can use to comply with the World Anti-Doping Agency`s mission of clean sport. LP: In equestrianism, there is a high injury incidence rate which could cause acute pain to the rider. Furthermore, the lifestyles which professional riders endure could also cause chronic pain to the rider. As a result, a study was conducted to establish the number of elite dressage riders competing with pain in the United Kingdom. 74% of elite dressage riders used in the study competed while experiencing pain. This information can provide British Dressage with an incentive to improve sports medicine, dressage ergonomics and rehabilitation techniques for the rider.